The Engineering of Non-Electrical Wheat Cracker Dough Cutting Tool - Sulharman, Sulharman; Sirait, Jantri; Saptaningtyas, Wara W.E. (IPTEK The Journal for Technology and Science, 2018)
The cracker cutter has been developed for many years, but still expensive, less effective, and not suitable Â for wheat cracker cutting. The purposes of this research is to design a tool for suitable cutting, cheap and non-electrical wheat crackers. The design apply using stainless wire and mechanism of the suppressor for cutting. To be able to engineer the tools, it is necessary to prepare materials such as iron elbow, stainless steel, iron plates, bolts, stainless wires, pipes polyvinyl chloride (pvc) and springs. Â The results show that an average cutting time about 12 kg/hour. In economic calculation there is discrepancies capacity per month 2060 kg or IDR. 123,600,000. There is an increase in capacity of 1700%.